Simulating a Virtual Reality-based Electrical Substation: A Pedagogical Proposal - Luna, Rafael; Castellucci, Frederico; Miranda, João Marcelo; Simeão, Mateus; Lyrio, Henrique; Soussa, Márcio; Winkler, Ingrid; Cesário, Frederico (Anais do Simpósio de Realidade Virtual e Aumentada (SVR); 2024: Anais do XXVI Simpósio de Realidade Virtual e Aumentada, 2024)
Virtual reality is a promising educational tool for electrical engineering because it can replicate complex environments. Immersive experiences can enhance knowledge retention and allow students to safely practice operation procedures and protocols, and develop their skills without the risks of handling high-voltage equipment. This work provides guidelines for developing a virtual reality-based simulation of an electrical substation for education. Using the design science research approach, we developed a three-stage educational simulation with progressive challenges and interactions in the Unity game engine and Meta Quest 2 device, and then an exploratory group evaluated the potential user acceptance and usage with the UTAUT2 model. Results highlighted that the simulation was intuitive and impacted positively on the learning process for the users while also being fun and engaging. Based on these encouraging outcomes, future classroom testing sessions will be conducted to further assess the impact of the simulation on the learning process.